Labor rights in the 2013 constitution of Vietnam and implementation prospects - Le, Thi Hoai Thu (Đại học Quốc gia Hà Nội, 2020)
In Vietnam, human rights, basic rights and duties of citizens are always respected and guaranteed. Together with human rights, labor rights are also recognized by the 2013 Constitution of Vietnam, in particular the right to work, the freedom to choose employment and place of work, the right to social security, the right to equal and safe working conditions for workers. The 2013 Constitution prohibits acts of discrimination, forced labor, use of workers under the labor age stipulated by the law. Besides recognizing these rights, the 2013 Constitution continues to affirm the Government’s duties to protect workers’ legitimate rights and interests, including measures to guarantee the implementation of workers’ rights. Many new rights of workers are recognized for the first time in the constitutional history of Vietnam, providing an important legal foundation for these rights to be institutionalized in specialized laws and under-law documents and to be complied with, as well as for proposing measures to protect and ensure the implementation of these rights in practice. However, internationalization, global integration and the fourth industrial revolution have been posing many challenges to guarantee workers’ rights in Vietnam. This requires the policies and laws on labor rights in Vietnam to be adjusted. The labor law needs to be amended to guarantee compatibility with fundamental international labor standards acknowledged in the international conventions and ratified by Vietnam. Furthermore, Vietnam needs to continue to review, ratify, and internalize ILO’s Conventions of which it has not been a member so as to guarantee and implement more effectively the labor rights of workers. In addition, the approach towards labor rights also needs to be changed in the direction of protecting legitimate rights and interests of both employers and employees. Regarding women workers, instead of protection, the labor law should be approached from the perspective of gender equality, promoting gender equality to guarantee women worker’s labor rights. With a human rights-based approach and mechanism for implementation, it will be increasingly promising for the future of labor rights recognized in the 2013 Constitution in Vietnam.